Paranoia, (Para)cinema, and the Right-Wing Mindset: Making Sense of My Son Hunter - Frykholm, Joel (American Studies in Scandinavia, 2024)
This article aims to make sense of My Son Hunter (The Unreported Story Society and Breitbart News, 2022; dir. Robert Davi). The first part of the analysis discusses My Son Hunter as an example of right-wing counter-cinema that tries to simultaneously tap into the cultural prestige associated with feature filmmaking and provide niche audiences with “paracinematic” pleasures. The second part of the analysis explores cinematic form and filmmaking techniques in My Son Hunter, demonstrating how the movie extends a promise of “truth” via an affective bombardment that draws on melodrama and paranoid fiction as well as the flexible modes of docudramatic approximation. The overall effect is to make logic and argumentation superfluous, which is indicative of how the film can be regarded as both symptomatic and productive of a “post-truth” condition.